Sectoral linkages and spillover effects: Can growth in manufacturing stimulate wider employment in South Africa? - Sanusi, Kazeem Abimbola; Dickason-Koekemoer, Zandri (Asian Journal of Economic Modelling, 2025)
This study examines whether growth in manufacturing output stimulates employment across South Africa’s broader economy, focusing on sectoral linkages and spillover effects. Anchored in the structural transformation literature, the analysis investigates the extent to which manufacturing acts as a catalyst for inclusive job creation beyond its own sector. Using quarterly time series data from 1963 to 2024 and applying a Structural Autoregressive Distributed Lag (SARDL) model, the study estimates both short-run and long-run effects across six sectors: manufacturing, construction, mining, financial services, trade, and public services. To account for exogenous shocks, interaction terms between manufacturing output and a COVID-19 dummy variable are included. The results reveal strong positive spillovers from manufacturing to employment in the construction, trade, and financial services sectors, while mining and public services exhibit limited responsiveness. Pandemic-induced disruptions significantly weakened these linkages, as evidenced by negative and significant COVID-19 interaction effects. The findings underscore manufacturing’s pivotal role in employment generation and support policies promoting manufacturing-led industrialization and intersectoral integration. This study contributes to debates on structural transformation and labor market dynamics in emerging economies. The study confirms that manufacturing remains a cornerstone of employment generation in South Africa, both within the sector and across the wider economy.